Da técnica à ética: olhar crítico de Hans Jonas para aconstrução de uma ética da responsabilidade. - Bezerra, Ednard Willams Alves (2024)
The present thesis seeks to undertand the relationship between Ethics and Responsability according to the work of Hans Jonas, based on the book: The Imperative of Responsability: In Search of an Ethics for the Technological Age. In addition, articles and periodicals that deal with the topic in focus – ethics. However, our research aims to study and reflect the issue of pre-modern technique and modern technique as a consequence the ethics of responsibility in Hans Jonas, considering that he brings an innovative understanding on fundamental questions, mainly related to the entire technological advancement of contemporary society. In Jonas’ assessment, it is stated that man needs to create a prevention strategy for the advancement and consequences of modern technology. For this motive we have the intention to investigate the historical context, cultural, social and educational aspects, considering the ethical dimension and moral values, from the humanistic perspective and construcion of today’s society. Consequently, we want to understand the impacts of human actions having the space in which they are located, and how human atitudes are also reflections on the environment of which they are part. Therefore, we hope that the process of hominization will be achieved through an education that aims to free man from all the ties that imprision him.